Anhedonia in depressed patients on treatment with selective serotonin reuptake inhibitor anti-depressant—A two-centered study in Malaysia. (August 2015) - Yee, Anne; Chin, Soo Cheng; Hashim, Aili Hanim bt; Harbajan Singh, Manveen Kaur A/P; Loh, Huai Seng; Sulaiman, Ahmad Hatim; Ng, Chong Guan
Abstract Objective. Anhedonia is the reduced ability to experience pleasure. It is a core symptom of depression and is particularly difficult to treat. This study aims to compare the level of anhedonia between depressed patients on anti-depressants and healthy subjects. Method. A total of 111 depressed patients on selective serotonin reuptake inhibitor (SSRI) and 82 healthy subjects were recruited from the outpatient psychiatric services at two major general hospitals in a cross-sectional study. Subjects were assessed using the Mini International Neuropsychiatric Interview 5.0.0 or MINI, Beck's Depression Index (BDI), and Snaith–Hamilton Pleasure Scale (SHAPS). Relevant personal and sociodemographic information were also collected. Results. There was a significant association between educational level and SHAPS-M scores (P < 0.01) among the participants. Most items in the SHAPS scores were significantly different (P < 0.01) in the depressed subjects treated with anti-depressant compared with the healthy subjects, after adjusting the confounding factors, BDI score, and educational level. Conclusion. Anhedonia often persists in depressed patients despite on SSRI anti-depressant treatment.